The Small Personal Triumph of the Homosexual Couple in "A Small Triumph” by Perry Brass - Asmarani, Ratna; Sanubarianto, Salimulloh Tegar; Fikri, Muhammad; Istiana, Inni Inayati (MOZAIK HUMANIORA, 2023)
This paper aims to expose the hidden value within the conventional homosexual narrative depicted in "A Small Triumph," a short story by Perry Brass. The analysis is underpinned by key concepts concerning homosexual relationships, gaydar, and Down Syndrome (DS). Employing a comprehensive approach, the study utilizes the library research method for data acquisition. The textual examination is concentrated on delineating the characters and conflicts, while the contextual approach employs concepts related to homosexuality and Down Syndrome to gain deeper insights into the characters and their conflicts. The overall analysis is presented through a qualitative lens. The findings elucidate the intricacies of the homosexual relationship between a youth with DS and an unsuccessful mature writer. Their mutual dependence catalyzes personal growth, with each taking turns to navigate the path towards their ultimate triumph as a homosexual couple.